2020
DOI: 10.30919/es8d912
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Dynamic Processes of Nanomaterials Using in Situ Liquid Phase TEM Technologies: 2014-2019

Abstract: The dynamic processes of nanomaterials are common phenomena in material science and biological system. Liquid-phase transmission electron microscopy (TEM) with high resolution provides unprecedented insights into dynamical processes by in situ imaging. This review summarizes the technical developments and the breakthroughs during 2014-2019 in the field of nanoparticles nucleation and growth, nanoparticles corrosion, self-assembly of nanomaterials, dynamical processes in vivo, in situ electrochemistry and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Future studies will include detailed modeling works including percolation theories, while rendering the composite PCMs multifunctional such as electromagnetic shielding properties by using modified nanoscale carbon hybrid fillers [59][60][61]. It is also important to understand and monitor the dispersion dynamics of the particles in the PCM during the heating-cooling cycles, newly developed technologies such as in situ liquid phase TEM analysis can be highly suitable for these materials systems [27]. In summary, these flexible (see Figure S3 and the video file; Supplementary Information), thermally conductive and stable PCM composites produced by solvent-free processes with easy scale-up potential can be very useful for different energy management systems ranging from modern electronic devices to energy savings in buildings [62,63].…”
Section: Thermal Properties Of the Monolithsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will include detailed modeling works including percolation theories, while rendering the composite PCMs multifunctional such as electromagnetic shielding properties by using modified nanoscale carbon hybrid fillers [59][60][61]. It is also important to understand and monitor the dispersion dynamics of the particles in the PCM during the heating-cooling cycles, newly developed technologies such as in situ liquid phase TEM analysis can be highly suitable for these materials systems [27]. In summary, these flexible (see Figure S3 and the video file; Supplementary Information), thermally conductive and stable PCM composites produced by solvent-free processes with easy scale-up potential can be very useful for different energy management systems ranging from modern electronic devices to energy savings in buildings [62,63].…”
Section: Thermal Properties Of the Monolithsmentioning
confidence: 99%
“…The use of PCMs in laminated composite structures has also made some advances recently [24]. Based on the recent review articles on PCM technologies, it can be argued that the development of form-stable, environmentally friendly organic PCMs modified with certain nanomaterials for increased thermal conductivity and structural stability is gaining high popularity among researchers [25][26][27]. Recent studies have found that combining metals with PCMs can significantly enhance heat storage performance due to much higher heat transfer coefficient of metals causing efficient heat transport.…”
Section: Introductionmentioning
confidence: 99%
“…Modern technologies have widened the vision of human wider than any time in the history: nanomaterials have never get so close to us before, from computer chips to targeting medications; [29,30] with the advanced instrumentations to visualize the nano-world, [31] we have seen the most amazing and beautiful science ever. What else surprises halide perovskite materials can give us in the next 10 years?…”
mentioning
confidence: 99%